DOUBLY DAMNED: THE EXPERIENCE OF HIV-POSITIVE MATERNITY - Morison, Tracy (PINS-Psychology in Society, 2025)
Long, Carol (2009) Contradicting maternity: HIV-positive motherhood in South Africa. Johannesburg: Witwatersrand University Press. ISBN 978-1-86814-494-5 pbk. Pages vii + 231. In Contradicting maternity, Carol Long argues that being both HIV-positive and a mother is a profoundly contradictory experience as the affirmative, idealised identity of mother collides with that of denigrated infected woman. She contends that the public portrayals of HIV-positive motherhood, which result in profound discomfort and negativity, have produced a caricature of maternal HIV that does not capture the complexity of the experiences of those who find themselves in this position. A major aim of the book, therefore, is to convey the complex and contradictory experiences of mothers who are HIV-positive and, importantly, to explore the topic from the point of view of the women themselves. It is based upon the experiences of “Black” South African HIV-positive mothers and mothers-to-be, many of whom discovered their status at the same time as hearing the news that they were pregnant. Long shows how these women’s personal responses to both their pregnancy and diagnosis intertwine with powerful public discourses around motherhood and HIV, as the spectre of the HIV-positive mother looms always as an abject, maligned, and marginalised identity.